Gut Microbiota – A Potential Contributor in the Pathogenesis of Bipolar Disorder - Zhang, Peifen; Kong, Lingzhuo; Huang, Huimin; Pan, Yanmeng; Zhang, Danhua; Jiang, Jiajun; Shen, Yuting; Xi, Caixi; Lai, Jianbo; Ng, Chee H.; Hu, Shaohua (Frontiers in Neuroscience, 2022)
Bipolar disorder (BD) is one of the major psychiatric disorders that is characterized by recurrent episodes of depression and mania (or hypomania), leading to seriously adverse outcomes with unclear pathogenesis. There is an underlying relationship between bacterial communities residing in the gut and brain function, which together form the gut-brain axis (GBA). Recent studies have shown that changes in the gut microbiota have been observed in a large number of BD patients, so the axis may play a role in the pathogenesis of BD. This review summarizes briefly the relationship between the GBA and brain function, the composition and changes of gut microbiota in patients with BD, and further explores the potential role of GBA-related pathway in the pathogenesis of BD as well as the limitations in this field at present in order to provide new ideas for the future etiology research and drug development.